Human settlements and urban development in Bangladesh - Islam, Nazrul; University of Dacca (Dhaka : University of Dhaka, 1998)
Part of the original papers were published in vol. 3 of the Report of the task forces on Bangladesh development strategies for the 1990's.
Includes bibliographical references and index
Keywords: Human settlements -- Bangladesh; Urbanization -- Bangladesh